"Other Mothers," Migration, and a Transnational Nurturing Nexus. - Bloch, Alexia (Signs: Journal of Women in Culture & Society)
Based on thirteen months of nonconsecutive ethnographic fieldwork (2001–11) among women labor migrants in Istanbul and their families in southern Moldova, this essay is framed by a critique of the forms of nurturing that are often portrayed as normative in discussions of transnational mobility. Patricia Hill Collins's foundational work on othermothering and her call for feminist scholarship to "shift the center" informs the analysis of three women's accounts of their experience of nurturing from a distance as they engage in transnational labor migration. Turning attention to local histories and practices, such as the "other mother" in southern Moldova, points to the distinctive ways nurturing can take shape in communities of outmigration. Moreover, the essay examines how historical experience of both local and Soviet state structures of caregiving, as well as the current virtual communication era, have brought about a distinctive transnational nurturing nexus, where caregiving for children is provided in multiple forms, including through remittances from women labor migrants, state-run day-care sites, and migrants' relatives. Ultimately, I argue that southern Moldovan nurturing practices, including mothering from a distance, or "other mothering," provide an important case for thinking about classic feminist questions about the diverse forms that motherhood and nurturing may take, as well as about the ways transnational mobility shapes local practices of nurturing.